Spaces for bohemian life in Lisbon - Vaz, C. (Urban Spaces and the complexity of cities, 2018)
For some time the “Commission Internationale pour l’Histoire des Villes“ has been working actively on the comprehensive topic of urban space which is also the aim of this book – result of conferences in Lisbon (2013) and in Clermont-Ferrand (2014). Two thematic priorities are presented in this combined English and French speaking volume: on the one hand cultural-symbolic spaces, on the other hand complexity of urban districts which formed in spite of all diversities collective cities. Continuous transformation of urban space and dichotomy shaped cities: Cities can be understood as space of town rulers, but also as space of a growing “bohème”. The chapter by C. Vaz addresses the spaces of so-called “bohemian life” in Lisbon between 1917 and 1927, focusing on their spatial localisation within the city, as well as on the organisation and the functions of their interior space, their representation in the press, literature and iconography.